Photovoltaic pumping tests: A novel supervision method for photovoltaic water pumping systems - Ange Sahuquet; Simon Meunier; Judith A. Cherni; Anne Charpentier; Thomas Vezin; Arouna Darga; Guillaume Zuffinetti; Peter K. Kitanidis; Loïc Quéval (Heliyon)
Water pumps powered by photovoltaic energy, often named ‘photovoltaic water pumping systems’ (PVWPS), offer a promising solution for improving water access in developing regions. Regular pumping tests are essential for characterizing boreholes and ensuring sustainable groundwater extraction. Traditionally, these tests are conducted only at the time of PVWPS installation using diesel pumps. However, since PVWPS typically have a lifespan of around 20 years, the borehole's condition may change over time, necessitating ongoing testing. To overcome this challenge, this article presents a novel method for conducting pumping tests using the PVWPS's own photovoltaic modules as the power source, greatly simplifying regular borehole monitoring over the PVWPS's lifespan. This approach improves the long-term technical sustainability of PVWPS. By eliminating the need for diesel generators, it reduces also costs, emissions, and logistical complexity while ensuring continuous water supply during testing. The principle and protocol for these proposed tests are outlined, as well as the key indicators for analysis. Furthermore, the associated costs and benefits are thoroughly explored. The proposed method is applied to a PVWPS in a village in Burkina Faso. This PVWPS has 750 Wp of photovoltaic modules, a 10 m³ water tank, and a 56 m borehole. Results show that the photovoltaic pumping tests allow to accurately determine borehole parameters, achieving a model fit with an average R2 of 0.99. Additionally, a photovoltaic pumping test costs $43, which is significantly lower than standard pumping tests: a multiple step drawdown test costs $511 and a long pumping test costs $2050. Moreover, the proposed photovoltaic pumping tests can prevent premature replacements of PVWPS components, leading to significant savings. While demonstrated in a specific context, this method is transferable to other systems, offering potential benefits for companies, local authorities, governments, and NGOs involved in the development and maintenance of PVWPS in rural areas.